A Padé-based fast frequency sweep approach for irregular large-scale building models subjected to seismic excitation. (December 2021) - Brambila de Salles, Humberto; Fadel Miguel, Leandro Fleck; Lenzi, Marcos Souza; Holdorf Lopez, Rafael
Highlights: A MOR scheme to compute the response of irregular buildings under seismic loads. The Padé-based FFS solves the dynamical response of controlled structures. SUFs up to 25 times can be reached in comparison with the direct solver. Abstract: Buildings with vertical or in-plane irregularities are often required for architectural purposes. From the seismic behavior perspective, such conditions usually demand a complete dynamic analysis instead of applying static equivalent lateral forces. Furthermore, a refined building's finite element model (FEM) can also be needed, leading to time-expensive computational solutions in the time domain. Despite cheaper, solving the system matrices repetitively over a broad frequency range in the frequency domain is an issue for large-scale systems too. Thus, this paper presents an efficient scheme, based on model order reduction (MOR), for computing frequency sweeps with fine increments of irregular buildings described by the FEM. In opposite to the standard Krylov-related MOR and SVD-based techniques, the Pade-based procedure employed herein can tackle any form of frequency dependency, as long as the high-order derivatives are obtained. For illustration purposes, a stiffness in-plane irregular H-shape building with 16452 active DOFs is solved using the MOR scheme for controlled and uncontrolled scenarios. Speed-up factors (SUF) up to 25 times can be reached for both cases when compared to direct frequency-domain solutions.